PENGEMBANGAN SUMBER DAYA MANUSIA DENGAN PENDEKATAN ADAPTIF UNTUK MENGHADAPI DINAMIKA LINGKUNGAN KERJA - Rahmatul Fitri; Abdur Razak (Mount Hope Management International Journal, 2024)
This research aims to analyze the development of Human Resources (HR) with an adaptive approach in facing the dynamics of an ever-changing work environment. In the era of globalization and rapid technological advances, companies are required to have human resources who are flexible and ready to face various challenges. This research uses literature study and literature review methods to identify the main concepts related to adaptive HR development, as well as the challenges and benefits that arise in its implementation. The research results show that an adaptive approach to HR development involves improving technical, social skills and the ability to adapt to change. Proactive management, support for relevant training programs, and the creation of an organizational culture that supports change are the main factors in the success of adaptive HR development. This research also found that although there are challenges, such as resistance to change, companies can overcome them with effective communication and employee empowerment. In conclusion, human resource development with an adaptive approach is an important long-term strategy to ensure the company's competitiveness and readiness to face future challenges